The Impact of Reviewers' Creditworthiness on Consumers' Purchase Intention in Edge Path: Implications for the Coronavirus Disease 2019 Pandemic - Limei, Chen; Wei, Liu (Frontiers in Public Health, 2020)
Reviewers' creditworthiness is an important edge clue in the Elaboration Likelihood Model (ELM). This paper takes the online travel booked by consumers as an example, uses the questionnaire data of 417 outbound passengers from Guangzhou Baiyun International Airport The paper examines the influence of reviewers' creditworthiness on consumer purchase intentions in the edge path through a mediated moderation model. Investigate the mediating role of conformity behaviour can influence the reviewers' creditworthiness on purchase. Thus it examines the moderating effect of consumer involvement. The results show that the degree of consumer involvement moderates the relationship between reviewers' creditworthiness and the purchase intention is achieved through the mediation of conformity behaviour. The higher the degree of consumer involvement, the less impact the reviewers' creditworthiness has on conformity behaviour, and the weaker the positive effects of its purchase intention are found. Implications for the COVID-19 era are also discussed.